Implementasi Model Pembelajaran STEAM (Science, Technology, Engineering, Art and Mathematics): Strategi Peningkatan Kecakapan Abad 21 - Eka Siti Barkah; Dodi Awaludin; Muhammad Iqbal El Asykuri Bahtiar (Syntax Corporation Indonesia, 2024)
The skills needed in the 21st century are indispensable in preparing students to face global challenges. The STEAM (Science, Technology, Engineering, Art and Mathematic) learning model links the fields of science, technology, engineering, art and mathematics, so that students gain a holistic understanding of the relationship between the fields of science through a 21st century educational approach. This journal will elaborate more deeply on 21st century skills associated with the STEAM learning model. The research method used in this article uses qualitative analysis. Data collection techniques through Library Research, namely by collecting references from books, articles, and journals related to the STEAM learning model and 21st century skills. STEAM is an interdisciplinary program that incorporates the arts into STEM and aims to improve students' critical thinking skills and creativity. The STEAM approach is grounded in math and science and is a discipline that focuses on discovery related to solving real problems through engineering or design methods. This approach looks at reshaping art exploration and encourages students to seek creative solutions. The STEAM method is contextualized learning that allows students to make sense of events happening around them. The STEAM method also integrates the field of study into the real world to help students understand the learning process.